A City of Betrayals: Irvine Welsh’s Minor Literature of Leith - Briand-Boyd, Julie (Complutense Journal of English Studies, 2021)
This article examines the representation of the city and communities of Edinburgh in Irvine Welsh’s works, more specifically his Trainspotting saga: Trainspotting (1993), Porno (2002), Skagboys (2012) and Dead Men’s Trousers (2018). While Welsh is an integral part of a broader literary tradition of the contemporary urban Scottish novel, which blends together the crime novel genre with the localised concerns of post-industrialism, gripping poverty, Thatcherite austerity, substance abuse and nagging questions of Scottish identity (gender, sexuality, class, nationhood, etc.), his depictions of the former port-town of Leith and its forgotten histories exposes Edinburgh as two distinctly separate and striated communities and geographies: one of opportunity and one of betrayal. Specifically, this essay reads Welsh through the literary, spatial and political theories of Gilles Deleuze and Félix Guattari with regard to Leith’s contentious historical relationship with Edinburgh. In this analysis of Welsh’s Leith as a vernacular, rhizomatic and anti-institutional force, this essay hopes to illustrate how Welsh’s work redirects the popular notions of Scottish national identity and statehood toward a minor literature, a linguistic, political and historical divergence from the dominant Scottish literary experience